Distanciamiento social por COVID-19 y su influencia en el desarrollo de depresión en adolescentes de la Unidad Educativa Ascázubi - Palacios Almeida, María Belén (2022)
Social distancing is a worldwide biosecurity measure that mitigates the spread of Covid-19. However, putting it into practice can provoke negative feelings that, when present in a vulnerable group such as adolescents, have repercussions on their mental state, causing them to go through depressive states, since they enter a period of persistent sadness and loss of interest in activities with which they normally felt pleasure. The purpose of this research was to determine how social distancing by Covid-19 influences the development of depression in adolescents at Ascázubi Educational Unit, with a descriptive, quantitative, cross-sectional and prospective cohort approach, with a sample of 425 students who met the inclusion criteria, to whom the Inventory of Social Distancing Compliance in teenagers and the Beck Depression Inventory II-A were applied, showing that there is predominance between social distancing compliance and minimum level of depression, with a value of 43.52%. On the other hand, there is a low prevalence between compliance with social distancing and a mild level of depression, with a value of around 5.88%. Likewise, it is evident that there is a low prevalence between compliance with social distancing and a moderate level of depression, at 4.70%. Finally, it is observed that there is a relationship between partial compliance with social distancing and severe level of depression, with a value of 3.05. It is concluded that there is no statistically significant relationship between social distancing and depression (p= 0.05)